A single-stranded DNA-based and terbium (III) fluorescent probe for facile and rapid detection of mercury (II). (February 2023) - Sun, Chunyan; Liu, Zheng; Ma, Xinyue; Yang, Chuanyu; Li, Ying; Liu, Ni; Lv, Ting; Wang, Junyang
Abstract: Hg 2+, as a highly dangerous pollutant, seriously affects public health and food safety. In this work, a biosensor based on single-stranded DNA and Tb 3+ fluorescent probe was constructed for facile and rapid detection of Hg 2+ . The detection method only needs one DNA strand, which consists of two parts: the G-rich sequence is the Tb 3+ luminescent antenna ligand and the T-rich sequence is the Hg 2+ recognition probe. Free mercury-specific DNA (MSD) in an aqueous solution could significantly enhance Tb 3+ luminescence. Upon the addition of Hg 2+, the conformation of MSD will switch from the free random coil structure to the hairpin structure. Thus, Tb 3+ was released and the fluorescence of Tb 3+ was decreased. After condition optimization, the change of fluorescence intensity was proportional to the logarithmic concentration of Hg 2+ from 0.01 to 10 μM with a detection limit of 1.9 nM. In addition, the detection results of Hg 2+ in real samples were satisfactory. The designed fluorescent probe has great advantages in simplicity and functionality and has great development potential in food safety and environmental pollution. Graphical abstract: Image 1 Highlights: This article contains the important innovations as following: A fluorescent sensor for Hg 2+ based on T-Hg 2+ -T conjugates and DNA-sensitized Tb 3+ . This assay requires only one unmodified oligonucleotide in one-test tube. It is simple, rapid and have good specificity and excellent anti-interference. This biosensor may sever as facile platforms for food and environmental analysis.